2005
DOI: 10.1002/pon.976
|View full text |Cite
|
Sign up to set email alerts
|

Patient delay in oral cancer: a qualitative study of patients' experiences

Abstract: Up to 30% of patients delay seeking the advice of a healthcare professional after self-discovery of symptom(s) of oral cancer. Reasons for this patient delay are poorly understood. The aim of the present study was to explore patients' initial experiences and reactions to developing symptoms of oral cancer, and to identify factors influencing their decision to consult a health care professional. In-depth semi-structured interviews were conducted with 17 consecutive patients who had received a diagnosis of oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 42 publications
3
98
0
1
Order By: Relevance
“…8 Early detection of oral cancer is key to reducing mortality and possible disfigurement, but previous studies have shown that patients delay seeing a health professional after noticing symptoms. 23 In the present study, most interviewees reported that they attempted some form of self-treatment before seeking help -and this process of self-treatment lasted anything from a few days to a few months. Interviewees purchased over the counter remedies (such as Bonjela) to treat inflammation, for example, or merely 'waited' to see if their symptoms would pass without intervention.…”
Section: Practice Delaymentioning
confidence: 60%
See 2 more Smart Citations
“…8 Early detection of oral cancer is key to reducing mortality and possible disfigurement, but previous studies have shown that patients delay seeing a health professional after noticing symptoms. 23 In the present study, most interviewees reported that they attempted some form of self-treatment before seeking help -and this process of self-treatment lasted anything from a few days to a few months. Interviewees purchased over the counter remedies (such as Bonjela) to treat inflammation, for example, or merely 'waited' to see if their symptoms would pass without intervention.…”
Section: Practice Delaymentioning
confidence: 60%
“…Both these concepts have been the subject of previous research with patients presenting with cancer or precancer [23][24][25]14 and particularly with younger people in Southern England. 8 Early detection of oral cancer is key to reducing mortality and possible disfigurement, but previous studies have shown that patients delay seeing a health professional after noticing symptoms.…”
Section: Practice Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…Most common reasons are the initial wrong diagnosis and the ignorance from the patient or from the attending physician. 10 Regarding this issue, a few study have been done in our country but this does not reflect actual scenario.…”
Section: Introductionmentioning
confidence: 99%
“…38 As early symptoms of oral cancer are often unspectacular, they are easily attributed to trivial causes by uninformed patients. 52 Socioeconomic status and barriers to access to a healthcare professional may be causes of patient delay, which is defined as the period between the patient first noticing a symptom and their first consultation with a healthcare professional concerning the symptom. 52 -54 Public awareness of oral cancer seems alarmingly low, as demonstrated by Horowitz et al, 55 who found that fewer than 25% of subjects could name alcohol or tobacco as risk factors.…”
Section: Causes Of Delaymentioning
confidence: 99%